The Level of Emotional Balance and its Relationship to the Quality of Life among Mothers of Children with Autism Spectrum Disorder in Karak Governorate - Al-Majali , Braah (Dirasat: Educational Sciences, 2024)
Objective: The study aims to evaluate the impact of emotional balance on the quality of life of mothers of children with autism spectrum disorder. Additionally, the study aims to examine the influence of maternal age and educational background on this emotional equilibrium. Methods: The study employed a correlational descriptive approach and utilized measures of emotional balance and quality of life to assess the sample of mothers of children with autism spectrum disorder. A randomly collected sample of 162 mothers in the Karak Governorate with children with autism spectrum disorders participated in the study. Results: The findings indicated that the level of emotional balance and quality of life among the participants was moderate. Furthermore, a positive correlation was observed between emotional balance and quality of life. Interestingly, the study revealed that the relationship between emotional balance and quality of life did not differ significantly based on the variables of the mother's age and educational level when considering mothers of children with autism spectrum disorder. Conclusions: The study put forward several recommendations, with the primary one being the organization of training courses and awareness programs by private centers for mothers of children with autism spectrum disorder in Karak Governorate. These programs aim to provide guidance and support, enabling mothers to enhance their emotional balance and improve their overall quality of life.